2019
DOI: 10.1002/pros.23927
|View full text |Cite
|
Sign up to set email alerts
|

The underestimated posterior lymphatic drainage of the prostate: An historical overview and preliminary anatomical study on cadaver

Abstract: BackgroundThe evidence of pelvic lymph node metastases after radical prostatectomy (RP) with pelvic lymph node dissection (PLND) is one of the strongest prognostic factors for poor oncologic outcome. The extent of PLND, although representing a crucial step in RP, is still controversial. Currently, there is a critical drawback in clinical practice due to the lack of congruence between the known lymphatic drainage and cancer dissemination despite defined management by a surgical approach. We hypothesized the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Based on TNM, inguinal and pararectal LNs should be considered as M1a and N1 disease, respectively 1 . This is also confirmed by studies investigating the pattern of lymphatic drainage of the prostate 20,21 . Adequately defining the extent of nodal disease is critical for correct completion of registries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on TNM, inguinal and pararectal LNs should be considered as M1a and N1 disease, respectively 1 . This is also confirmed by studies investigating the pattern of lymphatic drainage of the prostate 20,21 . Adequately defining the extent of nodal disease is critical for correct completion of registries.…”
Section: Discussionmentioning
confidence: 93%
“…1 This is also confirmed by studies investigating the pattern of lymphatic drainage of the prostate. 20 , 21 Adequately defining the extent of nodal disease is critical for correct completion of registries.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Boscolo-Berto et al . 12 reviewed the literature and experimentally dissected a human corpse with prostatic lymphatic drainage. Based on their study, there is a pararectal lymphatic plexus relating to the prostate in the direction of the lateral sacral lymph nodes, finally arriving at the common iliac and aortic lymphatic plexuses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Boscolo-Berto et al . 12 described that apart from the ascending ducts from the cranial gland leading to the external iliac nodes and the lateral ducts leading to the hypogastric nodes, lymphatic ducts from the posterior surface of the prostate were directed to the pararectal lymphatic plexus, leading to the lymphatic network around the common iliac artery and aorta. Notably, we previously performed a comparative study between ePLND and ICG-guided PLND and confirmed that ICG-guided PLND was able to provide a two-year metastasis-free survival rate of 100%, whereas conventional ePLND was able to provide a rate of 86%.…”
Section: Introductionmentioning
confidence: 99%
“…When PLND is performed during RP, especially when an extended template is adopted, complications may occur not only because of uncontrolled clamping of the lymphatic vessels but also because of small bleeding vessels originating from the muscular pelvic wall of the obturator fossa. Anatomic human variability of the vessels and the lymphatic pelvic system is also a factor that should considered during ePLND, as shown by anatomical studies investigating this subject [ 28 ]. As such, an ePLND may result in complicated lymphoceles or pelvic hematomas requiring subsequent invasive procedures.…”
Section: Discussionmentioning
confidence: 99%